2020
DOI: 10.1111/jocd.13390
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of bleomycin for treating keloid and hypertrophic scar: A systematic review and meta‐analysis

Abstract: Background Pathologic scars can lead to itching, erythema, and psychological stress due to cosmetic problems. Bleomycin, one of anticancer agents, has been used for treating keloid or hypertrophic scar. Some studies have shown that bleomycin can induce markedly scar improvement. Aims To evaluate the efficacy of bleomycin compared to corticosteroid as well as other treatments for keloid or hypertrophic scar using meta‐analysis methods. Methods A computerized search was performed in different databases including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 24 publications
0
23
2
Order By: Relevance
“…These results suggest that BLM is a more effective treatment option for keloid or hypertrophic scars than TAC and 5-FU or their combined therapies. However, the adverse reaction rate of BLM was higher (80). Interestingly, these findings are not in line with the current study's findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results suggest that BLM is a more effective treatment option for keloid or hypertrophic scars than TAC and 5-FU or their combined therapies. However, the adverse reaction rate of BLM was higher (80). Interestingly, these findings are not in line with the current study's findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, it significantly reduced post-injection pain ( 79 ). A recent meta-analysis evaluating the efficacy and safety of BLM, TAC, 5-FU, TAC combined with 5-FU, and TAC combined with cryotherapy found that BLM significantly improved the treatment of pathological scars than TAC or 5-FU combined with cryotherapy ( 80 ). There was no significant difference between the BLM group and the TAC combined with 5-Fu group.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis 99 of five trials showed that bleomycin injections improved hypertrophic scars and keloids more effectively than triamcinolone acetonide and/or 5-fluorouracil injections. A 14-study review on topical onion extract gel (a nonsteroidal antiinflammatory drug) reported that 11 detected beneficial effects on hypertrophic scars and keloids.…”
Section: Hypertrophic Scar Treatmentmentioning
confidence: 99%
“…At our tertiary academic hospital, we frequently treat patients with recalcitrant common warts, keloids, and hypertrophic scars with intralesional BLM using SLI 13,15 …”
Section: Discussionmentioning
confidence: 99%
“…In dermatological practice, jet injectors are used for intralesional delivery of triamcinolone acetonide for the treatment of hypertrophic scars, keloids, and alopecia areata 6–9 . Off‐label intralesional chemotherapy with jet injectors, however, have also shown efficacy, such as 5‐fluorouracil for the treatment of keloids and hypertrophic scars, methotrexate for non‐melanoma skin cancer, and bleomycin (BLM) for recalcitrant warts 10–15 . Of these chemotherapeutics, lung toxicity has been reported after high cumulative dosages of intravenous BLM (400 U) resulting in lung fibrosis 16,17 .…”
Section: Introductionmentioning
confidence: 99%